Experimental study of combustion and emission characteristics of diesel engine with diesel/second-generation biodiesel blending fuels. (1st August 2016) - Zhong, Wenjun; Xuan, Tiemin; He, Zhixia; Wang, Qian; Li, Da; Zhang, Xin; Huang, Yue Yin
Highlights: Combustion and emission characteristics for blended biodiesel was studied. PLIF technique was applied to study the OH distribution. High blending fraction of SGB indicates lower ignition delay. 20% blending ratios of SGB shows lower emissions as well as economy performance. Abstract: Second-generation biodiesel (SGB) is one of the next promising biofuels for internal combustion engines due to their advantages compared with the first-generation biodiesel (FGB). However, little research about SGB has been published on the optical diagnostics of their combustion processes and emissions characteristics. In this paper, the planar laser-induced fluorescence (PLIF) technique was applied to study the OH distribution in the flame of different blending ratios diesel/SGB in a constant volume chamber. The ignition delays under different operating conditions were observed by the high-speed imaging technique. After that, the emissions characteristics of those different blending ratios fuels were investigated in a four-cylinder direct injection diesel engine through ESC test cycle. The results show that the ignition delay decreased with increasing blending ratio of SGB and the LIF signal area increased with higher blending ratios of biodiesel. Furthermore, the blending fuel of IV_B20 has better emissions as well as economy performance among all fuels and HC emissions has little sensitivity towards the speed under the same load while NOx emissions at the same load are mainly depended on the engine speed.